2016
DOI: 10.1159/000452093
|View full text |Cite
|
Sign up to set email alerts
|

Community Perceptions of Biobanking Participation: A Qualitative Study among Mexican-Americans in Three Texas Cities

Abstract: Background: Most biospecimens in the US are collected from non-Hispanic Whites, limiting the generalizability of findings. There is a need to increase participation in biobanking among ethnic and racial minorities. The purpose of this study was to use qualitative methods to identify factors that may influence Mexican-American individuals' willingness to participate in biobanking. Methods: We conducted 15 focus groups in three Texas cities with Mexican-American individuals, in both Spanish and English. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 33 publications
5
58
0
Order By: Relevance
“…In this concern, several studies have been performed and many strategies have been suggested to increase participation of underrepresented populations 56 , 57 , 63 , 64 .…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this concern, several studies have been performed and many strategies have been suggested to increase participation of underrepresented populations 56 , 57 , 63 , 64 .…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Although the reasons underlying these observations have not been fully understood, it seems that differences in tumor genomics, health care access, disease detection, quality of treatment and lack of participation in health research may contribute to these outcomes 17 , 26 , 50 , 56 64 . For example, it has been estimated that approximately 1 per each 20 adult cancer patients participate in clinical trials; this rate persist over the time 65 and is significant lower among racial/ethnic minority groups 57 , 65 .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Hamilton et al (2016), personal motivation was a facilitator because PM may offer individual benefits such as getting a genetic test to learn if a person carries a specific genetic trait and using the test to identify the most effective treatment [35]. The focus group participants also mentioned altruism as the main reason to support the dissemination and adoption of PM for societal and scientific benefit, even if they did not benefit themselves, a finding found in another study [55].…”
Section: Facilitatorsmentioning
confidence: 88%
“…Securing patients understanding about biospecimen collection [13,15] and providing adequate and specific information that biospecimen collection will not only promote participants' trust in the research but will also enhance their participation in biospecimen collection research [13,15]. Finally, providing adequate information and open conversations about biobanking can increase participation in biospecimen collection [15,45].…”
Section: Discussionmentioning
confidence: 99%